2021
DOI: 10.1159/000517286
|View full text |Cite
|
Sign up to set email alerts
|

Does the Management of Visual and Audible Motion Information during an Immersive Virtual Reality Timed Up and Go Test Impact Locomotor Performance in the Elderly?

Abstract: <b><i>Background/Aims:</i></b> Falling among the elderly is a major public health issue, especially with the advancing age of the baby boomers. The fall risk assessment tests for many lack a context that would bring them closer to everyday life. Thus, immersive virtual reality, which makes it possible to simulate everyday situations, could make it possible to strengthen the quality of the assessment of the risk of falls. However, it is necessary to understand how the use of a virtual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
5
6
0
Order By: Relevance
“…Time and number of steps indeed increased whether it was a simple task such as Go and Return phases, or a more complex task such as Turn-Around and Sit-Down. These results were once again comparable with the ones measured with an elderly population [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Time and number of steps indeed increased whether it was a simple task such as Go and Return phases, or a more complex task such as Turn-Around and Sit-Down. These results were once again comparable with the ones measured with an elderly population [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it has been shown that dynamic postural control in adults can be affected by IVR compared to a real situation; increases center of pressure displacement and increases in motor response time have been recorded [ 15 , 16 ]. These results were consistent with two studies conducted by our research team, showing that an IVR effect was measured on elderly with a significant increase in time and number of steps parameters when performing a "Timed Up and Go" (TUG) locomotor task [ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations